Growth hormone in fertility and infertility: Mechanisms of action and clinical applications - Chang, Chia-Wei; Sung, Yu-Wen; Hsueh, Ya-Wen; Chen, Yi-Yan; Ho, Ming; Hsu, Hsi-Chen; Yang, Tung-Chuan; Lin, Wu-Chou; Chang, Hsun-Ming (Frontiers in Endocrinology, 2022)
Secreted by the anterior pituitary gland, growth hormone (GH) is a peptide that plays a critical role in regulating cell growth, development, and metabolism in multiple targeted tissues. Studies have shown that GH and its functional receptor are also expressed in the female reproductive system, including the ovaries and uterus. The experimental data suggest putative roles for GH and insulin-like growth factor 1 (IGF-1, induced by GH activity) signaling in the direct control of multiple reproductive functions, including activation of primordial follicles, folliculogenesis, ovarian steroidogenesis, oocyte maturation, and embryo implantation. In addition, GH enhances granulosa cell responsiveness to gonadotropin by upregulating the expression of gonadotropin receptors (follicle-stimulating hormone receptor and luteinizing hormone receptor), indicating crosstalk between this ovarian regulator and the endocrine signaling system. Notably, natural gene mutation of GH and the age-related decline in GH levels may have a detrimental effect on female reproductive function, leading to several reproductive pathologies, such as diminished ovarian reserve, poor ovarian response during assisted reproductive technology (ART), and implantation failure. Association studies using clinical samples showed that mature GH peptide is present in human follicular fluid, and the concentration of GH in this fluid is positively correlated with oocyte quality and the subsequent embryo morphology and cleavage rate. Furthermore, the results obtained from animal experiments and human samples indicate that supplementation with GH in the in vitro culture system increases steroid hormone production, prevents cell apoptosis, and enhances oocyte maturation and embryo quality. The uterine endometrium is another GH target site, as GH promotes endometrial receptivity and pregnancy by facilitating the implantation process, and the targeted depletion of GH receptors in mice results in fewer uterine implantation sites. Although still controversial, the administration of GH during ovarian stimulation alleviates age-related decreases in ART efficiency, including the number of oocytes retrieved, fertilization rate, embryo quality, implantation rate, pregnancy rate, and live birth rate, especially in patients with poor ovarian response and recurrent implantation failure.